RUBRIC FOR THE ASSESSMENT THE COMPETENCE OF INNOVATION CREATIVITY AND ENTREPRENEURSHIP IN BACHELOR DEGREE - Cuenca, Llanos; Alarcón, Faustino; Boza, Andrés; Fernández-Diego, Marta; Ruiz, Leonor; Gordo, MariLuz; Poler, Raul; Alemany, M.M.E. (Brazilian Journal of Operations & Production Management, 2016)
Innovation has a special value for the survival and development of organizations, especially in a changing context. The development of innovation capacity in students enhances their capacity to enter the workforce. A competency describes what training participants should be able to do at the end of the training. The competence is acquired through various learning outcomes to be achieved. Competition in innovation is closely related to the ability to propose and implement creative ideas to solve problems, ability to create and maintain connections work, etc. In this article is presented a method for measuring the competence of innovation creativity and entrepreneurship in bachelor degree by introducing different levels of scope.